A Qualitative Study to Investigate the Parental Perspectives on Children with Bedwetting - Noppe, Laura; Toelen, Jaan; De Rechter, Stéphanie (Belgian Journal of Paediatrics, 2025)
Objective: Nocturnal enuresis (NE) is a common condition in children. It is clinically defined as the involuntary urination of children aged five years or older, occurring at least twice per week over the past three months, in the absence of an identifiable somatic cause. NE affects not only the child with the condition, but also their wider environment and the well-being of their parents. This qualitative study aims to examine the repercussions of NE for parents and identify the specific daily life challenges they face as a result of their child's condition. Methodology: We conducted semi-structured interviews with parents of children experiencing NE. Participants were recruited after providing informed consent following paediatric nephrology consultations at University Hospitals Leuven or Regional Hospital Heilig Hart Leuven, both of which are located in Flanders, Belgium. Results: The study included interviews with 11 parents of children aged between 6 and 13 years old. Of these children, 64% were boys (n = 7) and 36% were girls (n = 4). Parents identified the impact of bedwetting on their children across three key domains: emotional well-being, social interactions and triggering factors. Furthermore, the effects on parents were categorised into five dimensions: parental concerns; the parent–child relationship; family dynamics; advice for other parents; and the influence of societal taboos. Conclusion: NE can affect various aspects of life for both children and their parents, potentially impacting their overall quality of life. It is therefore crucial for healthcare providers to openly discuss this issue to deliver comprehensive, holistic care.